Corporate carbon emissions and market value - Jinxu Zhang (Scientific Reports)
Abstract Driven by global low-carbon governance and China’s goals of carbon peaking and carbon neutrality, enterprises, as the main players in carbon emissions and economic development, are faced with the test of achieving a win-win situation between their own economic benefits and social benefits. This paper uses data of non-financial A-share listed companies in the Shanghai and Shenzhen stock exchanges from 2008 to 2018 to empirically examine the impact of corporate carbon emissions on firm value and its mechanism. The study finds that the higher the corporate carbon emissions, the lower the firm value. After tests using the difference-in-differences model, instrumental variable analysis, and placebo tests, the research results remain robust. Mechanism analysis shows that corporate carbon emissions have a negative impact on firm value by reducing the corporate risk-taking level, product market competitiveness, and the shareholding ratio of green investors. Further research reveals that the negative impact of corporate carbon emissions on firm value is more significant in enterprises with high agency costs, high real earnings management levels, and poor corporate social responsibility performance. The research contributions of this paper are mainly reflected in three aspects: first, it is the first to reveal the direct effect of carbon emission risks on firm value in the Chinese context, expanding the research dimension on the economic consequences of carbon emission risks; second, it enriches the research on factors affecting firm value and expands the boundary of theoretical interpretation; third, it explores the heterogeneous characteristics of how carbon emission risks affect firm value and defines the boundary conditions of the relationship between the two.